The role of dual-phase Tc-99m MIBI in the evaluation of potentially operable lesions detected by bone scanning in fibrous dysplasia: a long-term prospective follow-up study - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2012)
Purpose The aim of this study was to determine the role of whole-body Tc-99m MOP bone scintigraphy (BSc) with dual-phase Tc-99m MIBI scintigraphy (DPMSc) in the assessment of fibrous dysplasia (FD) and the value of DPMSc in the detection of potentially operable lesions for guiding surgical treatment. Methods Twelve patients with histopathologically confirmed FD were evaluated with BSc and DPMSc. The patients were clinically followed up for a mean duration of 75 months. BSc images have been used as a guide to identify the site and the extent of the skeletal involvement The symptomatic lesions were evaluated with DPMSc. Results Forty-three lesions were evaluated in 12 patients. BSc showed increased uptake in all of the lesions, whereas DPMSc findings correlated more accurately with the symptoms. Fifteen symptomatic lesions showed increased Tc-99m MIBI uptake on DPMSc, especially in the early phase of DPMSc. The sensitivity, specificity and accuracy values for the early phase in detecting the symptomatic lesions were 100 and 93%, and for delayed phase were 100 and 98%, respectively. Conclusion BSc is useful in determining the site and extent of the skeletal involvement, especially in polyostotic FD. It seems that the potentially operable symptomatic lesions may be evaluated more accurately with DPMSc as compared with BSc. In addition, it seems that DPMSc findings correlate with the symptoms of FD, and this relationship may have a role in improving the preoperative assessment for guiding surgical treatment DPMSc could be useful in the work-up of symptomatic patients if our results are validated in a larger patient series. Nucl Med Commun 33:288-296 (C) 2012 Wolters Kluwer Health | Lippincott Williams & Wilkins.
Keywords: fibrous dysplasia; radionuclide imaging; Tc-99m MIBI; Tc-99m MDP; MCCUNE-ALBRIGHT-SYNDROME; MAXILLARY SINUS; SCINTIGRAPHY; CYST; CT; SECONDARY; DISEASE; SURGERY; PATIENT; SKULL